VARIABILITY TO CARDIOPULMONARY EXERCISE TESTING IN PERSONS WITH ALZHEIMER'S DISEASE. (16th November 2018) - Salisbury, D; Yu, F
Abstract: Background. The purpose of this study was to investigate the effects of test duration of cardiopulmonary exercise test (CPET) on indicators of CRF and to explore relationships among CRF variables that are used to determinate if a peak test meets the criteria for being a maximal test in persons with Alzheimer's disease (AD). Methods. Seventy-eight community-dwelling older adults with mild-moderate AD (44 males [77.8 years and MMSE 21.3] and 34 females, [77.4 years and MMSE 21.6]) underwent a CPET on a cycle ergometer. Peak values from the metabolic cart, heart rate (HR) and rating of perceived exertion (RPE) were obtained during the last 30 seconds before cessation. Criteria for a maximal test were those listed by the American College of Sports Medicine. Results. There were no significant differences among peak values of oxygen consumption (VO2), HR, respiratory exchange ratio (RER), RPE, or achievement of VO2 max in tests that were under eight minutes, between 8–12 minutes, or over 12 minutes. Among indicators used in the assessment of VO2 max, in peak VO2 showed significant, positive correlations with peak HR (r=.46) and RER (r=.37), however peak RPE was not correlated with peak HR (r=.14), VO2 (r=.14) or RER (r=-.10). Conclusions. Our findings show that test duration did not yield significantly different peak HR, RPE, or RER values, suggesting the length of test may not be as important as previously thought. The use of RPE as a criterion for benchmarking the achievement of a max test may be inappropriate in AD populations.